RETRACTED ARTICLE: A Multilevel Fuzzy Evaluation of Cross-Border E-Commerce Profitability Model - Qijun Zou (International Journal of Computational Intelligence Systems, 2023)
Abstract With the continuous development of economic globalisation, China has established free trade zones (FTA). To promote the diversification of cross-border e-commerce in FTA and increase industry competitiveness, the Porter's Five Forces model (PFFM) was used to analyse the profit model of e-commerce enterprises. Based on fuzzy logic, an evaluation model for the profit model of cross-border e-commerce was constructed, and this evaluation model was used to evaluate the profitability of cross-border e-commerce. The results show that the evaluation model constructed based on fuzzy logic can better reflect the profitability of enterprises. The accuracy of multilevel fuzzy evaluation is above 80% every year, with the highest accuracy being in 2017, and the evaluation accuracy for that year is 98.5%. The study of a cross-border e-commerce profit evaluation model based on multilevel fuzzy evaluation method can better reflect the profitability of enterprises and help them clarify their future development direction.